Professional Qualifications, Job Experience and Employability of Teachers in Private Secondary Schools in Lagos State, Nigeria - Adetoro, J. A.; Adekunle, A. A. (International Journal of Educational Management, 2022)
This study examines the relationship among academic/professional qualifications, job experience and employability of teachers in private secondary schools in Lagos State, Nigeria. The non-compliance with the provision of the National Policy on Education of the possession of requisite qualifications in teaching by some of the graduates employed to teach in private schools has been worrisome. The study adopts a descriptive survey design. The sample size comprised 150 participants made up of proprietors and proprietresses of private secondary schools randomly selected from six local governments (3 representing sub-urban, and 3 representing urban). Questionnaire was the instrument used for data collection. The one-way Analysis of Variance statistics was used for data analysis. The study reveals that that there is a significant relationship between teachers' job experience and their employability in private secondary schools irrespective of the location. The findings also revealed that there is strong relationship between teachers' qualifications and their employability. It is therefore suggested among others that there is need for universities to expand their postgraduate programmes to accommodate more students for postgraduate studies so as to equip them for employment opportunities in the private secondary schools without hindrance.